Экспрессия энкефалина в паравентрикулярных ядрах гипоталамуса при экспериментальном диабете у крыс - Абрамов, А. В.; Карнаух, М. Н.; Абрамов, Андрій Володимирович; Карнаух, Марина Миколаївна; Abramov, A. V.; Karnaukh, М. N. (My University, 2014)
The article contains information about peculiarities of metand leu-ekephalin expression in different subnuclei of hypothalamic paraventricular nuclei (PVN) in the rats with experimental diabetes. It was established that normally enkephalin expression is observed in small amount of PVN neurons; the total amount of metenkephalin is 10 times more than leu-enkephalin amount. Diabetes development is accompanied by the increase of the quantity of neurons which express opioids, in the greater degree leu-enkephalin. Moreover, in the neurons of anterior and medial parvocellular subnuclei and posterior magnocellular subnucleus neurosecretion of opioids is inhibited, while in periventricular subnucleus neurosecretion is significantly activated. The mechanisms of enkephalinergic hypothalamic system adaptation to the conditions of metabolic disturbances, caused by diabetes mellitus are analyzed.
Enkephalin expression in the hypothalamic paraventricular nuclei in the rats with experimental diabetes
Keywords: enkephalins; diabetes mellitus; hypothalamus